The Effect of Compensation, Leadership, and Work Environment on Job Satisfaction of Employees of The Mangga Village Office, in Medan Tuntungan Sub-District - Sani, Ucok Syahputra; Nurholisr, Iman; Tammimi, Mhd Khairul; Ardini, Elsi; Tarigan, Nur M. Ridha; Yusrita, Yusrita (Universitas Medan Area, 2024)
This research aims to identify and analyze the influence of compensation, leadership and work environment on employee job satisfaction in Mangga Village, Medan Tuntungan District. Data was collected through a survey using a questionnaire distributed to employees in various work units in the area. The results of data analysis using the multiple regression method show that compensation, leadership and work environment have a significant influence on employee job satisfaction. Compensation that is fair and appropriate for employee contributions is identified as a factor that has a positive impact on job satisfaction. Apart from that, effective leadership and a conducive work environment also play an important role in increasing employee job satisfaction levels. This research contributes to understanding the factors that influence employee job satisfaction at the local level, especially in Mangga Village, Medan Tuntungan. The practical implications of this research can help organizational management and local governments improve working conditions and compensation policies to increase employee job satisfaction in the region. Further research is also recommended to expand the scope of variables or areas that can provide a more comprehensive understanding of the dynamics of employee job satisfaction at the local level.